Pengukuran Koefisien Transfer Massa Oksigen Pada Kolom Konis Dengan Aliran Berlawanan - Perpustakaan UGM, i-lib ([Yogyakarta] : Department of Chemistry Gadjah Mada University, 2000)
Estimation of the oxygen mass transfer coefficient is needed in design of aeration tank. The method recently used is monitoring the change of DO level in water body caused by introducing air in a given flow rate. In this research, oxygen mass transfer coefficient was obtained by monitoring single bubble dimension in a cone column with counter-current flow. Experiments were conducted for several dissolved oxygen (DO) level to observe the change of bubble dimension related to DO level. From this research, it is found that the oxygen mass transfer coefficient varies with bubble dimension.